7th International Conference on Structural Analysis of Historic Constructions : strengthening and retrofitting : selected, peer reviewed papers from the 7th International Conference on Structural Analysis of Historic Constructions, October 6-8, 2010, Shanghai, People's Republic of China - Gu, Xianglin; Song, Xiaobin (Advanced materials research., 2010)
Increasing urbanization constitutes a mounting threat to cultural heritage sites around the world; especially in developing countries. Natural and man-made environmental hazards are causing more damage to historic constructions than ever before. The conservation of historical constructions is facing new challenges introduced by waves of immigration and industrialization. The present papers on this subject are organized into two volumes, and the topics of interest span the entire spectrum of structural analyses of historic constructions: including Materials and Structural Configuration, Structu.